Comprehensive Analysis of Genes Associated With Sudden Infant Death Syndrome - Riffat Mehboob; Riffat Mehboob; Maher Kurdi; Mursleen Ahmad; Syed Amir Gilani; Sidra Khalid; Hisham Nasief; Abeer Mirdad; Husam Malibary; Sahar Hakamy; Amber Hassan; Meshari Alaifan; et al. (Frontiers Media S.A., 2021)
Background: Sudden infant death syndrome (SIDS) is a tragic incident which remains a mystery even after post-mortem investigation and thorough researches.Methods: This comprehensive review is based on the genes reported in the molecular autopsy studies conducted on SIDS so far. A total of 20 original studies and 7 case reports were identified and included in this analysis. The genes identified in children or adults were not included. Most of the genes reported in these studies belonged to cardiac channel and cardiomyopathy. Cardiac channel genes in SIDS were scrutinized for further analysis.Results: After screening and removing the duplicates, 42 unique genes were extracted. When the location of these genes was assessed, it was observed that most of these belonged to Chromosomes 11, 1 and 3 in sequential manner. The pathway analysis shows that these genes are involved in the regulation of heart rate, action potential, cardiac muscle cell contraction and heart contraction. The protein-protein interaction network was also very big and highly interactive. SCN5A, CAV3, ALG10B, AKAP9 and many more were mainly found in these cases and were regulated by many transcription factors such as MYOG C2C1 and CBX3 HCT11. Micro RNA, "hsa-miR-133a-3p" was found to be prevalent in the targeted genes.Conclusions: Molecular and computational approaches are a step forward toward exploration of these sad demises. It is so far a new arena but seems promising to dig out the genetic cause of SIDS in the years to come.